BRAND SWITCHING ANALYSIS IN HAND & BODY LOTION FOR WOMEN CONSUMERS : A CASE STUDY IN STUDENT OF FACULTY PHARMACY UGM - Tia Aningtyas; Sampurno Sampurno; Djoko Wahyono (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The causes of brand switching are dissatisfaction, the desire of variety and the influence of promotion. This type of research was associative study to analize link between customer dissatisfaction, need to find variations and the influence of promotion on brand Hand&Body Lotion, that causing the brand Switching Hand&Body Lotion. Location of research conducted at the Faculty of Pharmacy UGM, with sample Strata 1 (S1) student, Pharmacist and Master (S2) as many as 200 people. Determination techniques in non-probability sample used was purposive sampling or sampling based on the criteria, the student of Faculty of Pharmacy who using Hand & Body Lotion for 6 months. Data retrieval method used was a questionnaire. The analytical method used was multiple regression method. The result obtained was Y = -1,551 + 0,182X1 + 0,189X2 + 0,215X3 where Y was the displacement of the brand, X1 was the dissatisfaction of consumers, X2 was the need to find variation and X3 the influence of variations in the promotion. Equation can be interpreted that consumer dissatisfaction , needs to find the variety of products and promotional products significantly influenced the decision on Brand Switching Hand & Body Lotion (p <0.05). Promotion variables had the most impact on brand switching by consumers decision between the other independent variables under study that was equal to 0.215. The desire for a variation variable had a constanta 0,189 and 0,82 for advertisment variable.Keyword : Brand switching, dissatisfaction, variation, promotion